Impact of treatment for adolescent and young adults with essential thrombocythemia and polycythemia vera - Beauverd, Yan; Ianotto, Jean-Christophe; Thaw, Kyaw Htin; Sobas, Marta; Sadjadian, Parvis; Curto-Garcia, Natalia; Shih, Lee-Yung; Devos, Timothy; Krochmalczyk, Dorota; Galli, Serena; Bieniaszewska, Maria; Seferynska, Ilona; et al. (Leukemia, 2025)
Essential thrombocythemia (ET) and polycythemia vera (PV) are rare in adolescent and young adult (AYA). These conditions, similar to those in older patients, are linked with thrombotic complications and the potential progression to secondary myelofibrosis (sMF). This retrospective study of ET and PV patients diagnosed before age 25 evaluated complication rates and impact of cytoreductive drugs on outcomes. Among 348 patients (278 ET, 70 PV) with a median age of 20 years, the of thrombotic events was 1.9 per 100 patient-years. Risk factors for thrombosis included elevated white blood cell count (>11 × 109/L) (HR: 2.7, p = 0.012) and absence of splenomegaly at diagnosis (HR: 5.7, p = 0.026), while cytoreductive drugs did not reduce this risk. The incidence of sMF was 0.7 per 100 patient-years. CALR mutation (HR: 6.0, p < 0.001) and a history of thrombosis (HR: 3.8, p = 0.015) were associated with sMF risk. Interferon as a first-line treatment significantly improved myelofibrosis-free survival compared to other treatments or the absence of cytoreduction (p = 0.046). Although cytoreduction did not affect thrombotic event, early interferon use reduced sMF risk. These findings support interferon use to mitigate sMF risk in AYA ET and PV patients.
Keywords: mutace; dospělí; esenciální trombocytemie; primární myelofibróza; Female; Adult; mladý dospělý; ženské pohlaví; Adolescent; Calreticulin; lidé; trombóza; Thrombocythemia, Essential; Polycythemia Vera; Mutation; polycythaemia vera; následné studie; prognóza; Risk Factors; retrospektivní studie; Follow-Up Studies; Male; Young Adult; kalretikulin; Thrombosis; rizikové faktory; Prognosis; mužské pohlaví; Retrospective Studies; Primary Myelofibrosis; mladiství; Humans